COMMUNITY PARTICIPATION IN THE DEVELOPMENT OF PROCESSED FISH AS AN EXCELLENT PRODUCT OF LAUK BABAKAN VILLAGE - Sugih Setiawan, Aditya; Pratiwi Batubara, Rima (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Lauk Babakan Village is located in the Bogor City area, West Java Province. Lauk Babakan Village has been around since December 2019. This area is fed by the Cibenda River, which originates from the main Cisindangbarang river. Carrying the concept of clean times. The development of tourism in Lauk Babakan Village is in the form of processed products, one of which utilizes fish cultivation in the river. However, in the processing of fish products, the local community does not understand what preparations are best developed and how to package the products that are ready to sell. Meanwhile, the purpose of this study was to determine the community's response to participation in the development of processed fish products in Lauk Babakan Village. The method of implementing the development of processed fish in Lauk Babakan Village is designed for the period from August 2022 to September 2022. Community participation refers to the theory of forms of community participation, namely Therapy, Informing, Consultation, Placation, Partnership, Delegated Power, and Citizen Control. In the development of processed fish in Lauk Babakan Village, there are three stages of community participation in the form of Therapy, Informing, and Partnership.